2017
DOI: 10.1088/1742-6596/934/1/012050
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the Active Muon Shield for the SHiP Experiment at CERN

Abstract: Abstract. The SHiP experiment is designed to search for very weakly interacting particles beyond the Standard Model which are produced in a 400 GeV/c proton beam dump at the CERN SPS. The critical challenge for this experiment is to keep the Standard Model background level negligible. In the beam dump, around 10 11 muons will be produced per second. The muon rate in the spectrometer has to be reduced by at least four orders of magnitude to avoid muoninduced backgrounds. It is demonstrated that new improved act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…For SHiP, detailed simulations have shown that the number of background events is expected to be very low, so that the experiment is "background free" [35,[53][54][55]. For MATHUSLA, the background is also expected to be low [18,19], although no simulation studies of background have been performed.…”
Section: Contentsmentioning
confidence: 99%
“…For SHiP, detailed simulations have shown that the number of background events is expected to be very low, so that the experiment is "background free" [35,[53][54][55]. For MATHUSLA, the background is also expected to be low [18,19], although no simulation studies of background have been performed.…”
Section: Contentsmentioning
confidence: 99%
“…3. 1 By the term epoch, we mean a single full pass through the training dataset. When making k discriminator updates per single generator update, this implies that, per epoch, the generator is trained on 1 k+1 th fraction of the training data, while the discriminator -on the remaining k k+1 -th fraction.…”
Section: Results and Validationmentioning
confidence: 99%
“…For the GAN objective, we use the Wasserstein distance [42] with the gradient penalty term from [43], as we find it resulting in the best generated data quality. We train both generator and discriminator using RMSprop optimizer with learning rates starting at 0.0001 at the beginning of the training process and decreasing by a factor of 0.999 after each epoch 1 . We make 8 discriminator update steps per single generator step.…”
Section: Network Architecture and The Objective Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the muon shield is a crucial part of the experiment, it has undergone several rounds of optimisation utilising machine learning methods [6,7]. The goal of the optimisation was to maximise physics performance, while minimising shield length and cost.…”
Section: The Ship Detectormentioning
confidence: 99%